(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the role of modern educational technologies in enhancing independent learning among university students. It discusses how digital platforms, interactive learning tools, and learning management systems promote learner autonomy, improve motivation, and support individualized learning paths. The study highlights the pedagogical advantages of technology-assisted independent learning, analyzes current technological trends, and provides methodological recommendations for integrating modern tools into higher education. The findings suggest that the effective use of educational technologies significantly increases students’ self-regulation, critical thinking, and academic performance.